Social and Economic Rights in Uganda: Has the National Development Plan II (2015/16-2019/20) lived up to its Expectations? - Nabwowe Kasule, Angella; Mncwabe, Nokukhanya (Initiative for Social and Economic Rights (ISER), 2019)
Uganda’s Second National Development Plan (NDP II) 2015/16-2019/20 has as its theme ‘Strengthening Uganda’s Competitiveness for Sustainable Wealth Creation, Employment and Inclusive Growth.” The NDP II is the second in a series of six five-year Plans aimed at achieving Uganda Vision 2040, which envisions ‘A Transformed Ugandan Society from a Peasant to a Modern and Prosperous Country within 30 years.’ The NDP II has as its goal the attainment of middle-income status by 2020, pursuant of which the government implemented development strategies to strengthen Uganda’s competitiveness for sustainable wealth creation, employment and inclusive growth. To this end the Plan set itself four key objectives: (i) increasing sustainable production, productivity and value addition in key growth opportunities; (ii) increasing the stock and quality of strategic infrastructure to accelerate the country’s competitiveness; (iii) enhancing human capital development; and (iv) strengthening mechanisms for quality, effective and efficient service delivery. There was also a commitment to adopt a Human Rights Based Approach (HRBA) to implement the NDP II. The NDP II was expected to achieve results including: increasing GDP and per capita income; reducing poverty and inequality; reducing by at least 20% the number of young people not in education, employment or training; increasing urban and rural access to electricity and safe water; reducing the Infant Mortality Rate and the Maternal Mortality Ratio as well as child stunting in children under-5yrs, and; increasing the rate of primary to secondary school transition and Net Secondary Completion.